Three little truths [large type] - Shortall, Eithne (Wheeler Publishing, 2021)
"Martha used to be a force of nature: calm, collected, and in charge. But since moving her husband and two daughters to Dublin under sudden and mysterious circumstances, she can't seem to find her footing. Robin was the "it" girl in school, destined for success. Now she's back at her parents' with her four-year-old son, vowing that her ne'er-do-well ex is out of the picture for good. Edie has everything she could want, apart from a baby, and the acceptance of her new neighbors. She longs to be one of the girls, and to figure out why her perfect husband seems to be avoiding their perfect future. Three women looking for a fresh start on idyllic Pine Road. Their friendship will change their lives and reveal secrets they never imagined" --